Nanocrystalline calcium sulfate/hydroxyapatite biphasic compound as a TGF-β1/VEGF reservoir for vital pulp therapy. Issue 10 (October 2016) - Chiang, Yu-Chih; Chang, Hao-Hueng; Wong, Ching-Ching; Wang, Yi-Ping; Wang, Yin-Lin; Huang, Wen-Hsuan; Lin, Chun-Pin
Graphical abstract: Highlights: Multiple growth factors acted synergistically in biphasic compound. Controlled release of multiple growth factors from nCS/CS/HAp cement. Mineralization analysis of nCS/CS/HAp/TGF-β1/VEGF in vivo and in vitro . Abstract: Objectives: Vital pulp therapy aims to treat reversible pulpal injuries via protective dentinogenesis and to preserve more tooth structure. Mineral trioxide aggregate (MTA)-based capping materials demonstrate prolonged setting time increases the risk of pulpal infection during multi-visit treatment. Their non-degradable property occupies pulp space and limits dentin-pulp regeneration. This study reports an inorganic degradable biomaterial that presents a short initial setting time and acts as a growth factor reservoir to promote reparative dentinogenesis. Methods: We synthesize nanocrystalline calcium sulfate hemihydrate (nCS), hydroxyapatite (HAp) and calcium sulfate hemihydrate (CS) as a reservoir to which transforming growth factor-beta 1 (TGF-β1) and vascular endothelial growth factor (VEGF) are added (denoted as nCS/HAp/CS/TGF-β1/VEGF). In vitro biocompatibility and mineralization (the activity and expression of alkaline phosphatase, ALP) were evaluated. Rat animal model was created to test in vivo efficacy. Results: Cultured human dental pulp cells (HDPCs) showed that nCS/HAp/CS/TGF-β1/VEGF cement has excellent biocompatibility and the potential to elevate the activity and expression of ALP. The in vivo efficacy (rat animal model) indicates protective dentin by micro-computed tomography (μ-CT) measurements and histological analyses. The 3D μ-CT non-destructive analysis also determines volume changes during pulpotomy, suggesting that the degraded space of the nCS/HAp/CS/TGF-β1/VEGF cement is repaired by the formation of dentin-pulp tissue. Significance: These findings demonstrate that nCS/HAp/CS cement acts as a potent reservoir for the sustained release of growth factors, and that nCS/HAp/CS/TGF-β1/VEGF cement has a high potential to form the reparative dentinogenesis in vivo .